2016
DOI: 10.17235/reed.2016.3987/2015
|View full text |Cite
|
Sign up to set email alerts
|

Self-expanding metal stents in postoperative esophageal leaks

Abstract: Background: Postoperative esophageal leaks have a high morbidity and mortality. Self-expanding metal stents (SEMS) have been used as an alternative to re-operation.Aim: Evaluating predictors of success of SEMS in postoperative esophageal leaks.Methods: Retrospective study of patients with postoperative esophageal leaks referred for SEMS placement in a reference center during a period of 3 years. Technical success was defined as closure of the leak in barium swallow at 15 days. Clinical success was considered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…To comprehensively analyze the risk factors of anastomotic leak, first of all, it is emphasized that a precise and scrupulous surgical technique plays a decisive role in the healing of anastomotic tissue. Precise surgical operation needs to ensure firm and stable tissue closure, good blood supply to the stomach or other organs replacing the esophagus and targeted treatment of anastomotic tension 3–7 . At present, gastric conduit, especially the thin conduit replacing the esophagus, has been accepted by more and more surgeons.…”
Section: Complex Clinical Presentations and Possible Causes Of Anasto...mentioning
confidence: 99%
See 1 more Smart Citation
“…To comprehensively analyze the risk factors of anastomotic leak, first of all, it is emphasized that a precise and scrupulous surgical technique plays a decisive role in the healing of anastomotic tissue. Precise surgical operation needs to ensure firm and stable tissue closure, good blood supply to the stomach or other organs replacing the esophagus and targeted treatment of anastomotic tension 3–7 . At present, gastric conduit, especially the thin conduit replacing the esophagus, has been accepted by more and more surgeons.…”
Section: Complex Clinical Presentations and Possible Causes Of Anasto...mentioning
confidence: 99%
“…The principle of self expandable metallic stent (SEMs) in the treatment of gastrointestinal fistula is to use the released stent to support the tube wall and to block the defect, so as to achieve physical isolation and promote the healing of the leak. With the popularization of SEMs in clinical practice, more and more successful cases have been reported, but many stent‐related complications have also been reported, the most common of which are stent‐related bleeding, stent displacement, and lateral abscess of fistula, etc 22–24 . Some scholars have reviewed the treatment experience of 15 patients with tracheal fistula and found that five were secondary to stent.…”
Section: Esophageal Stentsmentioning
confidence: 99%
“…In the case of an AL with a larger defect than what a clip can treat, SEMS with adequate CT-Scan-guided drainage of the paraesophageal hole can close the defect and ensure oral feeding. Following an easy placement, the SEMS usually needs up to 24 h to fully expand [ 33 ]. On the other hand, some teams such as ours are more prone to use the EVT as a first step approach.…”
Section: Anastomotic Leakmentioning
confidence: 99%
“…Endoscopy plays an important role in the treatment of caustic esophageal strictures. Caustic stricture is often complex and difficult to dilate [10] . Early esophageal dilatation can be done after 3 weeks of caustic ingestion.…”
Section: Endoscopy In the Late Phasementioning
confidence: 99%